Plan de marketing para impulsar el crecimiento de la demanda de mercado con relación a los servicios en soluciones informáticas que la empresa Adexus S.A. brinda en la ciudad e Quito - Robayo Paredes, Oswaldo Alexander (2015)
This paper is based on the development of a marketing plan as a tool to increase market demand for the company Adexus S.A. in the city of Quito, whose business is marketing solutions due to rapid and continuous advancement of technology is vital to have an axis of operation to be clear operating guidelines for short and medium term. The thesis is divided into four chapters that present current information about the company and the environment in which it operates with this data analysis to develop strategies and actions to promote commercial activity of the company and establish a sustainable development can be conducted adapting existing changes in the Ecuadorian market. The information was obtained through field research and literature. Surveys were conducted on a sample of companies that are clients of Adexus SA Contrary opinions requesting the service and quality of products and services received by the company based on that identify critical factors for improvement.